The Effect Of Problem-Based Learning Model During Pandemic On The Thematic Learning Outcomes Of Students In Elementary School - Simamora, Diana Falentina; Manurung, Hisar Marulitua (Universitas Pahlawan Tuanku Tambusai, 2021)
This study aims to determine the effect of the Problem Based Learning learning model during the pandemic on the thematic learning outcomes of students in grade IV Private Primary School HKBP Tomuan with Science Subjects on theme 6 My ideals, sub-theme 1 I and my ideals, learning 2. Types This research is Classroom Action Research using 2 cycles with four stages, namely planning, action, observation, and reflection. The subjects of this study were the fourth-grade students of HKBP Tomuan Private Elementary School, totaling 20 people, while the object of this research was the thematic learning outcomes of students by applying problem-based learning models. The technique of collecting data is by observing and conducting a pretest at the beginning of learning and a posttest at the end of learning. Based on the analysis of the data obtained in the first cycle by not using the problem-based model, the learning outcomes of 12 students reached the KKM, namely 60 to 75%, and 8 students did not reach the KKM, which was